Pengaruh Diferensiasi Produk dan Citra Merek Terhadap Kepuasan Konsumen dan Penjualan Pada PT Aerofood Indonesia Cabang Kualanamu - Muhammad Aidil Iffat; Azhari Akmal Tarigan (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to determine the influence of brand image and product differentiation on sales at PT Aerofood Indonesia Kualanamu Branch and the extent to which product differentiation influences customer satisfaction at that location. Quantitative methods are applied. The population of this research is all customers who have used products and services from PT Aerofood Indonesia Kualanamu Branch. 110 respondents were given a questionnaire to fill out in order to do this. The findings of this research show that at PT Aerofood Indonesia Kualanamu Branch, product differentiation has a good and significant influence on customer satisfaction. However, at PT Aerofood Indonesia Kualanamu Branch, brand image does not have a real impact on customer satisfaction, either positively or negatively. At PT Aerofood, customer satisfaction and sales are significantly influenced by product differentiation and brand image.